Factors Associated With Availability of, and Employee Participation in, Comprehensive Workplace Health Promotion in a Large and Diverse Australian Public Sector Setting: A Cross-Sectional Survey. Issue 11 (November 2015) - Kilpatrick, Michelle; Blizzard, Leigh; Sanderson, Kristy; Teale, Brook; Venn, Alison
Abstract : Purpose: The aim of this study was to explore factors associated with the perceived availability of, and reported participation in workplace health promotion activities implemented in the Tasmanian State Service, Australia. Methods: Data from 3228 employees were collected in 2013 on sociodemographic and work characteristics, health-related behaviors, and employee-reported availability of and participation in health-related activities. Ratios of prevalence for reported availability and participation by each factor were estimated using negative binomial regression (availability) and Poisson regression (participation). Results: Significant differences in availability of different activity types were found for numerous factors. Compared with the reference categories, only administrative staff or respondents reporting any leisure-time physical activity were more likely to participate, and smokers and respondents with variable work schedules or cardiometabolic conditions were less likely. Conclusions: Employees with suboptimal health-related factors were less likely to engage with activities offered through this comprehensive workplace health promotion initiative.